1962
DOI: 10.1017/s002211206200124x
|View full text |Cite
|
Sign up to set email alerts
|

The motion of rigid particles in a shear flow at low Reynolds number

Abstract: According to Jeffery (1923) the axis of an isolated rigid neutrally buoyant ellipsoid of revolution in a uniform simple shear at low Reynolds number moves in one of a family of closed periodic orbits, the centre of the particle moving with the velocity of the undisturbed fluid at that point. The present work is a theoretical investigation of how far the orbit of a particle of more general shape in a non-uniform shear in the presence of rigid boundaries may be expected to be qualitatively similar. Inertial and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
501
0
1

Year Published

1966
1966
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 753 publications
(526 citation statements)
references
References 2 publications
24
501
0
1
Order By: Relevance
“…Numerical comparison of Stokes and inertial flow development along the channel near the pillar indicates that the presence of the pillars leads to deformation of streamlines and while this deformation possesses fore-aft symmetry in Stokes flow, in agreement with the mirror-symmetry time-reversal theorem 17 , the symmetry is broken in the presence of inertia (Fig. 2a).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Numerical comparison of Stokes and inertial flow development along the channel near the pillar indicates that the presence of the pillars leads to deformation of streamlines and while this deformation possesses fore-aft symmetry in Stokes flow, in agreement with the mirror-symmetry time-reversal theorem 17 , the symmetry is broken in the presence of inertia (Fig. 2a).…”
Section: Resultssupporting
confidence: 65%
“…Notably, this net twisting of fluid around a pillar has been neglected in microfluidic systems because fluid inertia is often not important in a wide range of conventional microfluidic flow conditions 16 . Flow around a pillar in a straight channel without inertia (that is, Stokes flow) requires fore-aft symmetry because of the mirror-symmetry of the flow upon timereversal of the linear equations of motion 17 . Therefore, any secondary fluid motion directed within the channel crosssection 18 is completely reversed after passing the cylinder mid-plane.…”
Section: Resultsmentioning
confidence: 99%
“…These theories predict a negative value for the coefficient K for pushers at low shear rates, meaning the suspension can exhibit a lower viscosity than the suspending fluid. The theoretical assessment of shear viscosity relies on an assumed statistical representation of the orientations of the bacteria, captured by a Fokker-Plank equation and a kinematic model for the swimming trajectories [25,26].Despite the large number of theoretical studies, few experiments have been conducted. With bacillus subtilis (pushers) trapped in a soap film Sokolov et al[12] have shown that a vorticity decay rate could be associated with a strong decrease of shear viscosity in the presence of bacteria.…”
mentioning
confidence: 99%
“…The discovery was verified by the subsequent experiment of Taylor. 34 Furthermore, Bretherton 35 extended Jeffery's conclusion to a revolution body, and demonstrated that the orientation of the axis of almost any body of revolution is a periodic function of time in any unidirectional flow. For a fiber, Jeffery's result induces the following equation:…”
Section: A Deterministic Rotational Dynamics Of Fibersmentioning
confidence: 95%